Analysis of the Effect of Adding Calcium Carbonate (CaCo3) Against the Compressive Strength of Light Bricks (Compressive Strength Analysis of Light Bricks Based on SNI Rules 03-3449-2002) - Sutria Desman; Hanifah Asnur (LEADER: Civil Engineering and Architecture Journal, 2024)
The use of lightweight bricks in construction is an effort to reduce the load on building structures and material consumption compared to traditional bricks. Lightweight brick, often also called lever brick, is a building material for walls that is much in demand in building construction. Lightweight bricks are made from a mixture of Portland cement, water, sand and foam. This research aims to determine the compressive strength of lightweight bricks without Calcium Carbonate and to determine the effect of adding Calcium Carbonate on the compressive strength of lightweight bricks. This research uses an experimental method using a quantitative approach. The results of testing the compressive strength of lightweight bricks aged 14 days produced an average compressive strength value for normal bricks of 0.7168 MPa, %5 calcium carbonate mixture of 0.6199 MPa, 10% calcium carbonate mixture of 0.5618 MPa, 15% calcium carbonate mixture % of 0.4843 MPa.